Geochemical characteristics of the Late Proterozoic Spitz granodiorite gneiss in the Drosendorf Unit (Southern Bohemian Massif, Austria) and implications for regional tectonic interpretations - Lindner,M.; Finger,F. (Journal of Geosciences, 2018)
The Spitz Gneiss, located near the Danube in the southern sector of the Variscan Bohemian Massif, represents a ˜13 km² large Late Proterozoic Bt ± Hbl bearing orthogneiss body in the Lower Austrian Drosendorf Unit (Moldanubian Zone). Its formation age (U-Pb zircon) has been determined previously as 614 ± 10 Ma. Based on 21 new geochemical analyses, the Spitz Gneiss can be described as a granodioritic I-type rock (64-71 wt. % SiO2) with medium-K composition (1.1-3.2 wt. % K2O) and elevated Na2O (4.1-5.6 wt. %). Compared to average granodiorite, the Spitz Gneiss is slightly depleted in Large-Ion Lithophile (LIL) elements (Rb 46-97 ppm, Cs 0.95-1.5 ppm), Sr (248-492 ppm), Nb (6-10 ppm), Th (3-10 ppm), the LREE (e.g. La 10-30 ppm), Y (6-19 ppm) and first row transitional metals (e.g. Cr 10-37 ppm). The Zr content (102-175 ppm) is close to average granodiorite. The major- and trace-element signature of the Spitz Gneiss is similar to some Late Proterozoic granodiorite suites in the Moravo-Silesian Unit (e.g. the Passendorf-Neudegg suite in the Thaya Batholith). However, granodiorites of such type and age do not occur elsewhere in the Moldanubian Zone of the Bohemian Massif. This observation fits existing tectonic models in which the Austrian Drosendorf Unit is considered allochthonous and part of the Moravo-Silesian Unit and the Avalonian Superterrane. Mineral chemistry data for amphibole, plagioclase and biotite allow an estimation of the Variscan peak regional metamorphic conditions for the Spitz Gneiss at ˜700 °C and 7 kbar. Amphibole and plagioclase show hardly any signs of retrograde reequilibration, implying a fast late-Variscan exhumation. Partial chloritization of biotite indicates late fluid activity at T ˜ 250 °C.
Keywords: Spitz Gneiss; Moldanubian; Bohemian Massif; Moravo-Silesian; Cadomian; Peri-Gondwana terranes